2006
DOI: 10.1021/ja057449i
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Sensors for Organophosphorus Nerve Agent Mimics

Abstract: We present a small molecule sensor that provides an optical response to the presence of an organophosphorus (OP)-containing nerve agent mimic. The design contains three key features: a primary alcohol, a tertiary amine in close proximity to the alcohol, and a fluorescent group used as the optical readout. In the sensor's rest state, the lone pair of electrons of the basic amine quenches the fluorescence of the nearby fluorophore through photoinduced electron transfer (PET). Exposure to an OP nerve agent mimic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
243
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 410 publications
(249 citation statements)
references
References 20 publications
3
243
0
3
Order By: Relevance
“…Exposure to an OP nerve agent mimic triggers phosphorylation of the primary alcohol followed rapidly by an intramolecular substitution reaction as the amine displaces the created phosphate. The quaternized ammonium salt produced by this cyclization reaction no longer possesses a lone pair of electrons, and fluorescence readout is observed as the nonradiative PET quenching pathway of the fluorophore is shut down (Dale et al, 2006). Anandakathir et al reported the synthesis of stilbene-based fluorophore, 3,4-dihydroxy-4'-aminostilbene (DHAS) for the detection of chemical warfare agents such as organophosphorus nerve gases.…”
Section: Fluorescence Based Detection Of Pesticides and Organo-phosphmentioning
confidence: 99%
“…Exposure to an OP nerve agent mimic triggers phosphorylation of the primary alcohol followed rapidly by an intramolecular substitution reaction as the amine displaces the created phosphate. The quaternized ammonium salt produced by this cyclization reaction no longer possesses a lone pair of electrons, and fluorescence readout is observed as the nonradiative PET quenching pathway of the fluorophore is shut down (Dale et al, 2006). Anandakathir et al reported the synthesis of stilbene-based fluorophore, 3,4-dihydroxy-4'-aminostilbene (DHAS) for the detection of chemical warfare agents such as organophosphorus nerve gases.…”
Section: Fluorescence Based Detection Of Pesticides and Organo-phosphmentioning
confidence: 99%
“…There have been many innovations for the detection of this species including colorimetric detection methods [7,8] surface acoustic wave devices [9,10], enzymatic assays [11], interferometry [12] and fluorescent sensors [13][14][15]. However, all are plagued by at least one limitation or other such as slow response, lack of selectivity, poor sensitivity, operational complexities or non-portability.…”
Section: Introductionmentioning
confidence: 99%
“…It is based on a surfactant system to solubilise sparingly soluble CWA and to increase rates of reaction with nucleophilic reagents. Swager 24 developed a sensitive, fluorescent chemosensor for the detection of nerve agents [22][23][24] . He showed that upon intramolecular cyclisation reaction of nerve agents, he could transform a flexible chromophore into a rigid delocalised system causing offon response in the micromolar concentration range.…”
Section: Introductionmentioning
confidence: 99%